A study of laryngeal gestures in Mandarin citation tones using simultaneous laryngoscopy and laryngeal ultrasound (SLLUS). (21st March 2014) - Moisik, Scott R.; Lin, Hua; Esling, John H.
<x content-type="archive" xml:space="preserve">Abstract</x> In this work, Mandarin tone production is examined using simultaneous laryngoscopy and laryngeal ultrasound (SLLUS). Laryngoscopy is used to obtain information about laryngeal state, and laryngeal ultrasound is used to quantify changes in larynx height. With this methodology, several observations are made concerning the production of Mandarin tone in citation form. Two production strategies are attested for low tone production: (i) larynx lowering and (ii) larynx raising with laryngeal constriction. Another finding is that the larynx rises continually during level tone production, which is interpreted as a means to compensate for declining subglottal pressure. In general, we argue that larynx height plays a supportive role in facilitating f0 change under circumstances where intrinsic mechanisms for f0 control are insufficient to reach tonal targets due to vocal fold inertia. Activation of the laryngeal constrictor can be used to achieve low tone targets through mechanical adjustment to vocal fold dynamics. We conclude that extra-glottal laryngeal mechanisms play important roles in facilitating the production of tone targets and should be integrated into the contemporary articulatory model of tone production.